On the concept and factors of the regional development - S. M. Khudoborodov; Ya. Yu. Radyukova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Within the framework of numerous goals of political programs at various levels, the category of «economic development» appears, but clear quantitative goals are not always set (and if they are set, it is often diﬃcult to trace their impact on “development”). This raises an important issue in the formulation of the very concept of “development” and the factors that ensure it.Goal. The purpose of this study is to provide a tangible assessment of the category “regional economic development” and highlight the factors of its implementation.Materials and methods. The study is based on an analysis of the works of domestic and foreign economists on the topics of regional development and regional growth.Results and discussion. The article examines various theoretical approaches to regional economic development. Various deﬁnitions of the concepts «region» and “regional development” are explored. The relationship between development and economic growth is revealed. The factors ensuring economic development are given, and their role and approaches to assessment are also indicated.Conclusion. Based on the results of the study, we can conclude that the source of breakthrough economic development, which is an important task for our country at the present stage, is innovation in competitive regional industries.